Communicative disorders in some minority pre-school and school-age children in u.s.a - James Monroe Stewart (Journal of All India Institute of Speech and Hearing)
The specific purposes of this study were to survey and to determine the number and prevalence of communicative disorders in a metropolitan, minority-based, comprehensive health-care facility. The rationales were developed from the limited and/or lack of accurate data on medical facilities, language disorders, and preschool children. The methodology included surveying the records for children referred Jor speech-language and audiological evaluations during the five-year calendar period 1973 through 1977. The results revealed that 3,827 children were seen for evaluation; of this number 38’ 5% were diagnosed with communicative disorders.